Circ‐MTO1 correlates with favorable prognosis and inhibits cell proliferation, invasion as well as miR‐17‐5p expression in prostate cancer. Issue 3 (11th November 2019) - Hu, Yijia; Guo, Bin
Abstract: Background: This study aimed to investigate circular RNA‐mitochondrial tRNA translation optimization 1 (circ‐MTO1) expression in tumor tissue and its correlation with clinical characteristics and survival profiles, as well as its effect on cancer cell functions in prostate cancer. Methods: A total of 298 primary prostate cancer patients were included. Reverse transcription‐quantitative polymerase chain reaction was conducted to evaluate circ‐MTO1 expression in tumor tissue and paired adjacent tissue. Disease‐free survival (DFS) and overall survival (OS) were recorded. In in vitro experiment, prostate cancer cells were transfected with circ‐MTO1 over‐expression and negative‐control over‐expression plasmids. Then cell proliferation, cell invasion and miR‐630 as well as miR‐17‐5p expressions in prostate cancer cells were detected. Results: Circular RNA‐mitochondrial tRNA translation optimization 1 expression was downregulated in tumor tissue compared with paired adjacent tissue ( P < .001) in patients with prostate cancer. Circ‐MTO1 high expression in tumor tissue was correlated with decreased pathological T stage ( P = .001) as well as lower pathological N stage ( P = .020). As for survival profiles, the DFS ( P = .006) and OS ( P = .018) were both longer in patients who had circ‐MTO1 high expression compared with patients who had circ‐MTO1 low expression. In addition, circ‐MTO1 high expression independently predicted favorable DFS and OS. Besides, further in vitro experiments illustrated that circ‐MTO1 inhibited proliferation ( P < .05) and invasion ( P < .05) as well as downregulated miR‐17‐5p expression in prostate cancer cells ( P < .05). Conclusion: Circ‐MTO1 correlates with decreased pathological T/N stage and favorable survival profiles, and it also inhibits cell proliferation, invasion as well as miR‐17‐5p expression in prostate cancer.